Handbook of Vascular Biometrics - Uhl, Andreas; Busch, Christoph; Marcel, Sébastien; Veldhuis, Raymond (Advances in Computer Vision and Pattern Recognition, 2020)
This open access handbook provides the first comprehensive overview of biometrics exploiting the shape of human blood vessels for biometric recognition, i.e. vascular biometrics, including finger vein recognition, hand/palm vein recognition, retina recognition, and sclera recognition. After an introductory chapter summarizing the state of the art in and availability of commercial systems and open datasets/open source software, individual chapters focus on specific aspects of one of the biometric modalities, including questions of usability, security, and privacy. The book features contributions from both academia and major industrial manufacturers.